O budowaniu zaplecza teoretycznego glottodydaktyki polonistycznej. Uwagi na marginesie Podstaw dydaktyki języka polskiego jako drugiego. Podejście integracyjno-inkluzyjne - Wioletta Hajduk-Gawron (Postscriptum Polonistyczne)
The article attempts to sum up the progress of research on glottodidactics in Polish studies, with particular regard to the inclusive approach in the context of students who have experienced migration. The basic source used was the book by P.E. Gębal Podstawy dydaktyki języka polskiego jako drugiego. Podejście integracyjno-inkluzyjne. [Fundamentals of teaching Polish as a second language. An integration- and inclusion-based approach]